Manuel Francisco Jiménez Ortiz and the construction of a Costa Rican power elite, 1900-1950 - Marchena Sanabria, Jorge (2023)
This article analyzes the historical construction of wealth in Costa Rica through the figure of businessman Manuel Jiménez Ortiz. The central argument of the paper is that Jiménez raised the level of his family and secured his position as an elite of power, thanks to the accumulation of material wealth, investments in different companies and productive activities, prestige, political participation, influence in the press and leadership of his oligarchic group. In addition, Jiménez's participation was key in several of the most transcendental historical processes of the first half of the 20th century. A power elite approach is used as groups that combine different attributes, are built over time, and have a high concentration of wealth and privilege. To carry out this work, archive documents, writings by Jiménez, hemerographic sources and other bibliographical references were used; Jiménez's career, his main investments and political positions were reconstructed.